Mechanical, thermal and physical properties of natural fiber reinforced composites for 3D printer - Fused Deposition Modeling: a review - Ahmad, Mohd Nazri; Ishak, Mohamad Ridzwan; Md Yasir, Ahmad Shah Hizam (Elsevier Editora, 2025)
Additive manufacturing (AM) or 3D printing technology is a method for building three-dimensional parts through the sequential addition of material layers according to a digital blueprint. It differs from subtractive manufacturing, which entails the removal of material to form an object. In the fields of research and manufacturing domains, fused deposition modeling (FDM) has received the greatest attention. The use of natural fibers as fillers for thermoplastic composites in 3D printing has drawn interest, which has led to a quest for more environmentally friendly production techniques. Careful techniques and a thorough understanding of the characteristics of natural fibers and their matrices are necessary for the fabrication of natural fiber reinforced thermoplastic composites for FDM. Thus, this paper reviews the properties of natural fiber reinforced thermoplastic composites for FDM based 3D printing. It covers the literature and findings on mechanical, thermal and physical properties of natural fiber reinforced thermoplastic composites for FDM based 3D printing. Finally, conclusions regarding required properties of natural fibers for FDM based 3D printing are also discussed. This review article provides readers with a complete understanding of the advantages and properties of natural fiber reinforced composites FDM based 3D printing. As the demand for sustainable materials continues to grow, the potential for these composites to contribute to eco-friendly manufacturing practices becomes significant.